Improving the utility of the Brunnstrom recovery stages in patients with stroke: Validation and quantification. Issue 31 (August 2016) - Huang, Chien-Yu; Lin, Gong-Hong; Huang, Yi-Jing; Song, Chen-Yi; Lee, Ya-Chen; How, Mon-Jane; Chen, Yi-Miau; Hsueh, I-Ping; Chen, Mei-Hsiang; Hsieh, Ching-Lin
Abstract : Abstract: The Brunnstrom recovery stages (the BRS) consists of 2 items assessing the poststroke motor function of the upper extremities and 1 assessing the lower extremities. The 3 items together represent overall motor function. Although the BRS efficiently assesses poststroke motor functions, a lack of rigorous examination of the psychometric properties restricts its utility. We aimed to examine the unidimensionality, Rasch reliability, and responsiveness of the BRS, and transform the raw sum scores of the BRS into Rasch logit scores once the 3 items fitted the assumptions of the Rasch model. We retrieved medical records of the BRS (N = 1180) from a medical center. We used Rasch analysis to examine the unidimensionality and Rasch reliability of both upper-extremity items and the 3 overall motor items of the BRS. In addition, to compare their responsiveness for patients (n = 41) assessed with the BRS and the Stroke Rehabilitation Assessment of Movement (STREAM) on admission and at discharge, we calculated the effect size (ES) and standardized response mean (SRM). The upper-extremity items and overall motor items fitted the assumptions of the Rasch model (infit/outfit mean square = 0.57–1.40). The Rasch reliabilities of the upper-extremity items and overall motor items were high (0.91–0.92). The upper-extremity items and overall motor items had adequate responsiveness (ES = 0.35–0.41, SRM = 0.85–0.99), which was comparable to that of the STREAM (ES = 0.43–0.44, SRM = 1.00–1.13). The results of our study support the unidimensionality, Rasch reliability, and responsiveness of the BRS. Moreover, the BRS can be transformed into an interval-level measure, which would be useful to quantify the extent of poststroke motor function, the changes of motor function, and the differences of motor functions in patients with stroke.